2011
DOI: 10.1590/s0037-86822011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B marker seroprevalence and vaccination coverage in adolescents in the City of Itajaí, State of Santa Catarina, Southern Brazil, in 2008

Abstract: Introduction: Hepatitis B infection constitutes an important cause of morbidity and mortality worldwide. In Brazil, however, the current epidemiological situation is not clear. Considering the importance of establishing this prevalence, the aim of this study was to determine the prevalence of HBV markers in voluntary adolescents, junior high (secondary school) students, in the City of Itajaí, State of Santa Catarina, Brazil. Methods: A seroepidemiological, transverse study was conducted with 353 randomly chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
3
9
0
2
Order By: Relevance
“…Additionally, this prevalence is also similar to the rate found in adolescents with immunization rates up to 98% in the state (1.4% and 0.6%) Tonial et al, 2011), the rate reported in Portugal for adolescents with a mean age of 14 years old (0.6%) (Antunes, Macedo, Estrada, 2004), and the rate reported in Italy for individuals up to 24 years old (1.0%) (Fabris et al, 2008); however, it is inferior to the rate reported by Nascimento et al (2008) in first-time eligible blood-donors from north, northeast and southeast Brazil (2.9%) and to the rate found in blood donors in south Brazil (15.6%) (Martelli et al, 1999) and the MRF (4.5%) (Rosini et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, this prevalence is also similar to the rate found in adolescents with immunization rates up to 98% in the state (1.4% and 0.6%) Tonial et al, 2011), the rate reported in Portugal for adolescents with a mean age of 14 years old (0.6%) (Antunes, Macedo, Estrada, 2004), and the rate reported in Italy for individuals up to 24 years old (1.0%) (Fabris et al, 2008); however, it is inferior to the rate reported by Nascimento et al (2008) in first-time eligible blood-donors from north, northeast and southeast Brazil (2.9%) and to the rate found in blood donors in south Brazil (15.6%) (Martelli et al, 1999) and the MRF (4.5%) (Rosini et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…[23][24][25]29,30 However, it is important to point out that the comparison of results is difficult as the maintenance of anti-HBs titers may be influenced by the time elapsed since vaccination and the level of exposure to hepatitis B virus. 31 The rates of HIV-infected individuals who develop anti-HBs levels ≥10 IU/L after receiving the standard, accelerated, or four double-dose schedules are variable, ranging from 38.7% to 91.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term maintenance of immune memory is highly advantageous as it can provide an immediate response to pathogens to which the host has been previously exposed. Despite the level of anti-HBs after inoculation with three doses of the HBV vaccine (<10 IU/L; Livramento et al, 2011;Scaraveli et al, 2011;Tonial et al, 2011), the implementation of the universal HBV vaccination program significantly reduced the incidence of HBsAg carriers and HBV-related diseases (Chongsrisawat et al, 2006;Tosun et al, 2011). The survival of a memory cell has the potential to continuously stimulate the antigen.…”
Section: Discussionmentioning
confidence: 99%